Ectopic pancreatic adenocarcinoma in Meckel’s diverticulum: a case report - Shoichi Inokuchi; Kohjiro Shirabe; Satoshi Tsutsumi; Hiroomi Takayama; Takahiro Terashi; Kazuhiro Yasuda; Masahiko Ikebe; Toshio Bandoh; Junpei Wada; Shogo Urabe; Tohru Utsunomiya (Surgical Case Reports)
Abstract Background Malignant neoplasms arising from Meckel’s diverticulum are rare and an adenocarcinoma in Meckel’s diverticulum originating from ectopic pancreatic tissue is even rarer. Herein, we report a patient with an ectopic pancreatic adenocarcinoma in Meckel’s diverticulum who was successfully treated with surgery and chemotherapy. Case presentation A woman in her sixties presented to another hospital with abdominal pain. Plain computed tomography suggested an abdominal tumor and she was referred to our hospital. Enhanced computed tomography revealed a 23-mm low-density tumor in the abdominal cavity. Surgery was performed with a tentative diagnosis of a mesenteric tumor, such as a gastrointestinal stromal tumor, schwannoma, or lymphoma. First, we inspected the peritoneal cavity with a laparoscope. This revealed numerous nodules in the small bowel mesentery, suggesting peritoneal dissemination. A 20-mm-diameter white tumor was found in the small intestine and diagnosed as a small intestinal cancer. The small intestine was partially resected laparoscopically through a small skin incision. The patient’s postoperative course was uneventful, and she was discharged on postoperative day 9. Pathological examination revealed well-differentiated adenocarcinoma in the small intestine. The tumor had developed from a sac-like portion protruding toward the serosal side and had a glandular structure lined with flattened atypical cells. Neither pancreatic acinar cells nor islets of Langerhans were evident, suggesting a Heinrich type 3 ectopic pancreas. The final diagnosis was an adenocarcinoma originating from an ectopic pancreas in Meckel’s diverticulum. After a smooth recovery, the patient commenced chemotherapy for pancreatic cancer. Conclusions We present a very rare case of ectopic pancreatic carcinoma in Meckel’s diverticulum.